UPAYA PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI PEMBIMBINGAN WORKSHOP KELOMPOK MGMP SMKN 9 TEBO - JONI AFRIZAL (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve the ability of teachers in preparing learning implementation plans through workshop guidance for the School MGMP group in Senior High Schools (SMA) at SMK Negeri 9 Tebo, Jambi Province. This study uses the type of school action research. The results of this study indicate that teachers in the target schools have been able to prepare RPP by making correctly in terms of including subject identity, competency standards, basic competencies, indicators of competency achievement, clarity of formulation of learning objectives that do not cause multiple interpretations and contain learning outcomes behavior, selection teaching materials that are in accordance with the objectives and characteristics of students, organizing teaching materials in terms of completeness, systematics, material and suitability with time allocation, conclusions on the use of learning methods, clarity of scenarios of learning steps in terms of the introduction, core and closing as well as the completeness of the learning outcomes assessment instrument (question). , key, scoring guidelines) ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan guru dalam menuyusun rencana pelaksanaan pembelajaran melalui pembimbingan worshop kelompok MGMP Sekolah di Sekolah Menengah Atas (SMA) di SMK Negeri 9 Tebo Provinsi Jambi. Penelitian ini menggunakan jenis penelitian tindakan sekolah. Hasil penelitian ini menunjukan bahwa guru di sekolah binaan sudah dapat menyusun RPP dengan membuat dengan benar dalam hal mencantumkan identitas mata pelajaran, standart kompetensi, kompetensi dasar, indicator pencapaian kompetensi, kejelasan perumusan tujuan pembelajaran yang tidak menimbulkan penafsiran ganda dan mengandung perilaku hasil belajar, pemilihan materi ajar yang sesuai dengan tujuan dan karakteristik peserta didik, pengorganisasian materi ajar dalam hal ketuntasan, sistematika, materi dan kesesuaian dengan alokasi waktu, kesimpulan penggunaan metode pembelajaran, kejelasan skenario langkah pembelajaran dalam hal pendahuluaninti dan penutup serta kelengkapan instrument penilaian hasil belajar yaitu (soal, kunci, pedoman penskoran)